2020
DOI: 10.1108/ijm-08-2019-0407
|View full text |Cite
|
Sign up to set email alerts
|

Do green HRM practices influence employees' environmental performance?

Abstract: PurposeRecent research has demonstrated an increasing awareness among business communities about the importance of environmental concerns. Green human resource management (GHRM) has become a crucial business strategy for organizations because the human resource department can play a key role in going “green.” This study tests an integrative model incorporating the indirect effects of GHRM practices on employee organizational citizenship behavior toward environment (OCBE), through green employee empowerment. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
303
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 289 publications
(323 citation statements)
references
References 72 publications
18
303
0
2
Order By: Relevance
“…Different experts proposed several dimensions of GHRM. The present study usedfour dimensions of GHRMproposed by Renwick et al (2016).GHRM brings positive EPR by influencing OCBE-O in employees (Hameed et al, 2020;Luu, 2019). As far as OCBE-Ois concerned,"it is the voluntary act of employees towards accomplishing organizational environmental goals" (Robertson & Barling, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Different experts proposed several dimensions of GHRM. The present study usedfour dimensions of GHRMproposed by Renwick et al (2016).GHRM brings positive EPR by influencing OCBE-O in employees (Hameed et al, 2020;Luu, 2019). As far as OCBE-Ois concerned,"it is the voluntary act of employees towards accomplishing organizational environmental goals" (Robertson & Barling, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Shen, Dumont [47] put further light on green HRM scholarship and found that it affects employee intention of not to quit through organizational identification. Moreover various sustainability performance reflections like environmental performance, social performance and economic performance were effected by green HRM paradigm like Hameed, Khan [29] confirmed the enhancing of environmental performance by Green HRM paradigm, similar studies were conducted by [10,41,[48][49][50][51] to increase organizational performance.…”
Section: Effects Of Green Hrm: An Overviewmentioning
confidence: 78%
“…In spite of various reflections/ dimension in Green HRM paradigm, literature has unanimously debated six most important reflections which are green recruitment, green selection, green training, green development, green performance management and green rewards and compensation. Contrary to this, the conceptualization of Green HR reflected on various aspects, for instance enhancing environmental performance [29], organizational attractiveness [30], development of employee green behavior [31]. Moreover Jackson, Renwick [5] also conceptualized green HR and indicated to merge its functions with environmental management.…”
Section: Reflections Of Green Hrm: An Overviewmentioning
confidence: 98%
See 1 more Smart Citation
“…Wastes on the roads are a constant threat to humans, the environment, and other living creatures’ health. Such poor solid waste management causes various diseases and environment-related issues (Hameed et al, 2020; Lew, 2019). Due to a limited budget, the GOP is being criticized for spending billions on garbage disposal, whereas limited funds are available for people’s health.…”
Section: Critical Review Of Wte In Pakistanmentioning
confidence: 99%